Novel mutations in the SGCA gene in unrelated Vietnamese patients with limb-girdle muscular dystrophies disease - Chung Tran, Nam; Lien, Nguyen Thi Kim; Ta, Thanh Dat; Nguyen, Van Hung; Tran, Huy Thinh; Van Tung, Nguyen; Xuan, Nguyen Thi; Huy Hoang, Nguyen; Tran, Van Khanh (Frontiers in Genetics, 2023)
Background: Limb-girdle muscular dystrophy (LGMD) is a group of inherited neuromuscular disorders characterized by atrophy and weakness in the shoulders and hips. Over 30 subtypes have been described in five dominant (LGMD type 1 or LGMDD) and 27 recessive (LGMD type 2 or LGMDR). Each subtype involves a mutation in a single gene and has high heterogeneity in age of onset, expression, progression, and prognosis. In addition, the lack of understanding of the disease and the vague, nonspecific symptoms of LGMD subtypes make diagnosis difficult. Even as next-generation sequencing (NGS) genetic testing has become commonplace, some patients remain undiagnosed for many years. Methods: To identify LGMD-associated mutations, Targeted sequencing was performed in the patients and Sanger sequencing was performed in patients and family members. The in silico analysis tools such as Fathmm, M-CAP, Mutation Taster, PolyPhen 2, PROVEAN, REVEL, SIFT, MaxEntScan, Spliceailookup, Human Splicing Finder, NetGene2, and Fruitfly were used to predict the influence of the novel mutations. The pathogenicity of the mutation was interpreted according to the ACMG guidelines. Results: In this study, six patients from four different Vietnamese families were collected for genetic analysis at The Center for Gene and Protein Research and The Department of Molecular Pathology Faculty of Medical Technology, Hanoi Medical University, Hanoi, Vietnam. Based on clinical symptoms and serum creatine kinase (CK) levels, the patients were diagnosed with limb-girdle muscular dystrophies. Five mutations, including four (c.229C>T, p.Arg77Cys; exon one to three deletion; c.983 + 5G>C; and c.257_258insTGGCT, p.Phe88Leufs*125) in the SGCA gene and one (c.946-4_946-1delACAG) in the CAPN3 gene, were detected in six LGMD patients from four unrelated Vietnamese families. Two homozygous mutations (c.983 + 5G>C and c.257_258insTGGCT) in the SGCA gene were novel. These mutations were identified as the cause of the disease in the patients. Conclusion: Our results contribute to the general understanding of the etiology of the disease and provide the basis for definitive diagnosis and support genetic counseling and prenatal screening.